Human Resource Management Strategies in Welcoming the Digital Education Era in High Schools: A Literature Review - Riinawati, Riinawati; Noor, Fatwiah (FKIP Universitas Lampung, 2024)
Abstract: Human Resource Management Strategies in Welcoming the Digital Education Era in High Schools. The purpose of this study is to delve into effective human resource management (HRM) strategies essential for embracing the digital education era in senior high schools. Employing a literature review methodology, this research synthesizes existing scholarly works to illuminate the key HRM strategies conducive to successful adaptation to digital education environments. The findings of this literature review highlight several pivotal HR management strategies that have been identified as instrumental in facilitating the adoption and success of digital education initiatives in high schools. These strategies include robust professional development programs aimed at enhancing educators' digital skills, fostering a collaborative culture that encourages knowledge sharing and innovation among education staff, ensuring access to strong technical support to empower teachers in navigating technological challenges confidently, fostering visionary leadership that provides direction and support for innovative practices, and implementing supportive strategic policies to facilitate effective and sustainable technology adoption across the institution. In conclusion, the synthesis of literature underscores the critical importance of effective HR management strategies in preparing high schools to navigate the challenges and capitalize on the opportunities presented by the rapidly evolving digital education landscape. By leveraging insights gleaned from existing scholarly works, this study contributes to a deeper understanding of the role of HRM in facilitating successful transitions to digital education environments in senior high schools, particularly within the context of South Kalimantan. Keywords: human resource management, digital education, management strategy.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202409